1998
DOI: 10.1063/1.368425
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence studies of localized gap states in colloidal ZnS nanocrystals

Abstract: Effect of polydispersity, bimodality, and aspect ratio on the phase behavior of colloidal platelet suspensions J. Chem. Phys. 137, 134906 (2012) Autonomous colloidal crystallization in a galvanic microreactor J. Appl. Phys. 112, 074905 (2012) Colloidal cluster crystallization dynamics J. Chem. Phys. 137, 134901 (2012) Position-displacement correlations in QELSS spectra of non-dilute colloids J. Chem. Phys. 137, 124901 (2012) Photoluminescence dynamics in solid formulations of colloidal PbSe quantum dots:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
274
3
21

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(319 citation statements)
references
References 19 publications
21
274
3
21
Order By: Relevance
“…They have reported PL emission from the samples at 580 nm. However, the well-known blue emission peak observed at 445 nm in our samples is associated with the defectrelated emission of the ZnS host, the peak at 476 nm is attributed to sulfur bonds dangling at the interface of ZnS NPs and the green PL peak at 520 nm observed in this work is assigned to elemental sulfur species on the surface of ZnS (Tiwari et al 2010;Denzler et al 1998). The origin of the fourth PL peak in our samples is due to Mn 2?…”
Section: Methodsmentioning
confidence: 49%
See 1 more Smart Citation
“…They have reported PL emission from the samples at 580 nm. However, the well-known blue emission peak observed at 445 nm in our samples is associated with the defectrelated emission of the ZnS host, the peak at 476 nm is attributed to sulfur bonds dangling at the interface of ZnS NPs and the green PL peak at 520 nm observed in this work is assigned to elemental sulfur species on the surface of ZnS (Tiwari et al 2010;Denzler et al 1998). The origin of the fourth PL peak in our samples is due to Mn 2?…”
Section: Methodsmentioning
confidence: 49%
“…occurs and makes the forbidden transition of 4 T 1 -6 A 1 partially allowed, as a result the yellow-orange PL originates from a transition between the 4 T 1 excited state and the 6 A 1 ground state of the Mn 2? ion within a nanocrystalline ZnS lattice (Bhargava et al 1994;Denzler et al 1998;Ren et al 2008;Cao et al 2009). Therefore, by comparing these studies and our results it is concluded that in our synthesized samples Mn 2?…”
Section: Methodsmentioning
confidence: 99%
“…Similar emissions have previously been reported for ZnS nanobelts and attributed to Mn 2+ contamination. 3,4 These authors also reported EDX and TEM results which suggested their product was highly pure. That there is no trace of this orange luminescence in our samples prepared by Method B indicates that this may be a result of the significant twinning observed in the Method A sample.…”
Section: Fluorescence Of Znsmentioning
confidence: 91%
“…In solids, there is a tendency for a certain type of defect to arise due to different energy of their formation. For the ZnS nanoparticles the emission wavelength below 430 nm has been reported for the transitions involving interstitial states [34]. Since the excess of sulfur ions was present for the ZnS formation within polyion matrix, the emission at 410 nm may be assigned to the transitions arising from the interstitial states of sulfur atoms.…”
Section: Figure 8 Pl Spectra Of the Zns Nanoparticle In Polyion Matrmentioning
confidence: 99%